Personel Administration at Faculty of Education Souphanouvong University - NORDALA, Phouvong (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
The purposes of this research are: 1). To study about the administration of personnel at the Faculty of Education, Souphanouvong University. 2) To compare the administrators’ opinions and the teachers’ which was classified by genders, educational qualifications, positions and working experience. 3). To find out the guidelines how to improve the administration of personnel. The target groups consisted of 62 people, including 28 administrators and 34 teachers. The questionnaire was used as a research tool to collect data for this research. The SPSS program was used to analyze data to find out the frequency, means (  ), percentagse and standard values ( ). In addition, the t-test and F-test were also used to test to find out the differences. Theresearch results were as follows: 1) The participation levels of personnel administration in the Faculty of Education, Souphanouvong University included four components were generally at a good level (   3.70; = 0.90). 2) The comparison results of opinions which was classified by genders, educational qualifications, positions and work experience were found that the over all and each component were not statically significant difference because the p-value was smaller than .05.